Integrative transcriptome-proteome approach reveals key hypoxia-related features involved in the neuroprotective effects of Yang Xue oral liquid on Alzheimer’s and Parkinson’s disease - Chen, Xiang-Yang; Cheng, Ming-Rong; Tang, Chen-Chen; Xu, Chen-Qin; Zhong, Yi-Lang; Gao, Yuan; Cheng, Xue-Xiang; Chen, Jian (Frontiers in Pharmacology, 2024)
This study investigates the role of hypoxia-related genes in the neuroprotective efficacy of Yang Xue oral liquid (YXKFY) in Alzheimer's disease (AD) and Parkinson's disease (PD). Using differential expression and weighted gene co-expression network analysis (WGCNA), we identified 106 and 9 hypoxia-associated genes in AD and PD, respectively, that are implicated in the transcriptomic and proteomic profiles. An artificial intelligence-driven hypoxia signature (AIDHS), comprising 17 and 3 genes for AD and PD, was developed and validated across nine independent cohorts (n=1713), integrating 10 machine learning algorithms and 113 algorithmic combinations. Significant associations were observed between AIDHS markers and immune cells in AD and PD, including naive CD4+ T cells, macrophages, and neutrophils. Interactions with miRNAs (hsa-miR-1, hsa-miR-124) and transcription factors (USF1) were also identified. Single-cell RNA sequencing (scRNA-seq) data highlighted distinct expression patterns of AIDHS genes in various cell types, such as high expression of TGM2 in endothelial cells, PDGFRB in endothelial and mesenchymal cells, and SYK in microglia. YXKFY treatment was shown to repair cellular damage and decrease reactive oxygen species (ROS) levels. Notably, genes with previously dysfunctional expression, including FKBPL, TGM2, PPIL1, BLVRB, and PDGFRB, exhibited significant recovery after YXKFY treatment, associated with riboflavin and lysicamine. These genes are suggested to be central to hypoxia and neuroinflammation responses in AD and PD, and are potential key mediators of YXKFY's neuroprotective action.